Assessing bias and knowledge gaps on seed ecology research: implications for conservation agenda and policy - Ribeiro, Guilherme V T; Teixido, Alberto L; Barbosa, Newton P U; Silveira, Fernando A O (Ecological applications, 2016)
Sampling biases permeate ecological research and result in knowledge gaps that have vital consequences for conservation planning. The consequences of knowledge gaps on species identity and distribution (the Wallacean and Linnean shortfalls, respectively) have become apparent recently, but we know little about the extent that research biases and knowledge gaps on traits that influence species' niches (the Hutchinsonian shortfall) affect conservation policy. To examine whether knowledge of species' traits based on seed ecology is geographically, phylogenetically, and ecologically biased, we retrieved research data on seed germination, seed dormancy, seed dispersal, seed banks, seed predation, and seed removal from a database of 847 papers, 1648 species, and 5322 cases. Brazil was selected as a model system for megadiverse, undersampled countries. Kernel density maps showed that research was geographically biased towards highly populated sites, with vast areas remaining historically unexplored. We also show that research was clustered into protected areas. We detected a significant positive phylogenetic bias at genus-level, indicating research concentration in few genera and lower relative bias rates for many herbaceous genera. Unexpectedly, information on seed banking was available for only 74 (3.4%) of threatened species, which suggests that information deficits are highest for species with critical needs for ex situ conservation strategies. Tree, fleshy-fruited, and biotic dispersal species were disproportionately overstudied. Our data indicate that information deficits on seed ecology preclude our ability to effectively restore ecosystems and to safeguard endangered species. We call for a systematic improvement of environmental agenda in which policy makers and scientists target sites, clades, and functional groups historically neglected. Lessons from developed countries and collaborative efforts will be important for megadiverse, underdeveloped countries to achieve the targets of international agreements that depend on seed ecology knowledge aiming to secure biological diversity and ecosystem services.